2021
DOI: 10.1007/s10530-021-02615-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and relatedness in aquaculture and marina populations of the invasive tunicate Didemnum vexillum in the British Isles

Abstract: Introductions of invasive, non-native species in the marine environment are increasing as human activity within coastal areas rises. Genetic datasets are useful tools to identify source populations, track routes of invasions, and illuminate the role of genetic variation in the establishment and subsequent spread of novel introductions. Here, a microsatellite dataset is used to estimate the genetic diversity and population structure of 7 introduced Didemnum vexillum populations in Britain and Ireland, 4 of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
1
0
0
Order By: Relevance
“…In Brittany, where this seaweed is largely distributed, and particularly conspicuous in marinas, a SNP‐based study revealed a patchy genetic structure most likely explained by anthropogenic transport in and out of ports (here marinas), inducing low levels of differentiation either between distant or close locations (Guzinski et al, 2018 ). Similar patterns of mosaic genetic structure unrelated to distance, and including long‐distance dispersal events related to boating, have been reported for other species with short‐lived larvae, such as the sea‐squirt Ciona intestinalis in its native range in the English Channel (Hudson et al, 2016 ), the cosmopolitan and cryptogenic tunicate B. schlosseri in Canada (Lacoursière‐Roussel et al, 2012 ) or the colonial invasive tunicate Didemnum vexillum (Prentice et al, 2021 ). We note that exceptions to this observation exist, such as the spread of the ascidian Styela plicata in harbors along the Spanish coasts (Pineda, Lorente, et al, 2016b ).…”
Section: Ports Are Opening New Corridors Favoring Genetic Reshufflingsupporting
confidence: 61%
“…In Brittany, where this seaweed is largely distributed, and particularly conspicuous in marinas, a SNP‐based study revealed a patchy genetic structure most likely explained by anthropogenic transport in and out of ports (here marinas), inducing low levels of differentiation either between distant or close locations (Guzinski et al, 2018 ). Similar patterns of mosaic genetic structure unrelated to distance, and including long‐distance dispersal events related to boating, have been reported for other species with short‐lived larvae, such as the sea‐squirt Ciona intestinalis in its native range in the English Channel (Hudson et al, 2016 ), the cosmopolitan and cryptogenic tunicate B. schlosseri in Canada (Lacoursière‐Roussel et al, 2012 ) or the colonial invasive tunicate Didemnum vexillum (Prentice et al, 2021 ). We note that exceptions to this observation exist, such as the spread of the ascidian Styela plicata in harbors along the Spanish coasts (Pineda, Lorente, et al, 2016b ).…”
Section: Ports Are Opening New Corridors Favoring Genetic Reshufflingsupporting
confidence: 61%